How do shocks to bank capital affect lending and growth? - Eero Tölö; Paavo Miettinen (Bank of Finland, 2018)
We examine bank capital shocks using a recent new approach based on non-normal errors in vector autoregressive models. Using a sample of 14 European economies over January 2004 through March 2018 we identify two distinct classes of bank capital shocks, capital tightening shocks, and bank profitability shocks. We find that both bank capital shocks frequently lead to changes in lending volume and interest rates for new loans. In contrast to some recent similar studies, we find less evidence for impact on production. Bank capital shocks have further effects on the substitution between the bank and market-based financing and on credit allocation across different borrower sectors. Policymakers may find these results useful when considering counter-cyclical adjustments to the bank capital requirements.
URN:NBN:fi:bof-201811282145
Keywords: C11; C32; C54; 330